The politics of the Charter : the illusive promise of constitutional rights - Petter, Andrew (University of Toronto Press, 2010)
The Politics of the Charter is vividly written, free of legal jargon, accessible to a broad readership, and will provoke renewed discussion about how best to achieve a more compassionate and egalitarian Canadian society.